Improvement of red-pigment-producing fungal strain (Monascus purpureus FTC 5391) using monospore isolation technique - Abdul Manan, Musaalbakri; Ariff, Arbakariya; Mohamad, Rosfarizan; Abdul Karim, Mohamed Ismail (Malaysian Agricultural Research and Development Institute (MARDI), 2006)
Monospore isolation technique was performed to obtain the improved strain that has high and consistent ability to produce red pigment. The ability of Monascus purpureus FTC 5391 wild strain in producing red pigment was successfully improved using monospore isolation technique. By using this approach of improvement, three different monospore isolates of M. purpureus FTC 5391 (MP 3, MP 4 and MP 5) were obtained as the best red pigment producers when glucose, potato starch and rice starch were used as carbon source, respectively.